2011
DOI: 10.17221/1430-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Czech cold-blooded horses: genetic parameters, breeding value and the influence of inbreeding depression on linear description of conformation and type characters

Abstract: Genetic parameters, breeding values and inbreeding depression for 22 linear type description of conformation and type characters and 4 body measurements were evaluated in a group of 1744 horses of three original cold-blooded breeds in the Czech Republic in a long period of 18 years (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007). Based on the values of Akaike's information criterion, residual variance and heritability coefficient, a model with fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
7
5
0
2
Order By: Relevance
“…Vostrý et al (2011a) found average values of the inbreeding coefficient (F X ) to be 7.3% in the Old Kladruber horse. Similar results were published by Vostrý et al (2011b) on Czech cold-blooded breeds of horses.…”
Section: Breeding Valuessupporting
confidence: 90%
“…Vostrý et al (2011a) found average values of the inbreeding coefficient (F X ) to be 7.3% in the Old Kladruber horse. Similar results were published by Vostrý et al (2011b) on Czech cold-blooded breeds of horses.…”
Section: Breeding Valuessupporting
confidence: 90%
“…In our study, inbreeding depression was observed for nearly all the morphological and gait traits analyzed, but its effects on functionality were negligible. For HW, the observed effect of inbreeding was similar to that reported by Vostry et al (2011) for Czech cold-blooded horses, but much lower than the value reported by Gomez et al (2009) for the Andalusian horse. For morphological traits, where we estimated negative consequences of inbreeding, there is no clear pattern established for other horse breeds, such that significant inbreeding depression has been reported in some studies (Gomez et al, 2009;Vostry et al, 2011) while other authors have found no appreciable effects of inbreeding (Curik et al, 2003;Sierszchulski et al, 2005;Wolc and Balinska, 2010).…”
Section: Tablesupporting
confidence: 77%
“…For HW, the observed effect of inbreeding was similar to that reported by Vostry et al (2011) for Czech cold-blooded horses, but much lower than the value reported by Gomez et al (2009) for the Andalusian horse. For morphological traits, where we estimated negative consequences of inbreeding, there is no clear pattern established for other horse breeds, such that significant inbreeding depression has been reported in some studies (Gomez et al, 2009;Vostry et al, 2011) while other authors have found no appreciable effects of inbreeding (Curik et al, 2003;Sierszchulski et al, 2005;Wolc and Balinska, 2010). Nevertheless, it could be anticipated that the effect of inbreeding on morphological traits would be small, as these are expected to be less affected by inbreeding depression than fitness-related traits (DeRose and Roff, 1999).…”
Section: Tablesupporting
confidence: 77%
See 1 more Smart Citation
“…head length and width or face width, Table 2) were also discriminative between males and females, allowing us to clearly distinguish between the two sexes. A relative comparison of PRMe population with other horse breeds indicates that they generally have a height at the wither greater than other horse breeds of a similar body weight, such as the Mangalarga Marchador horse (148.31 cm; Pinto et al 2008) or the Lipizzan horse (155.11 cm; Zechner et al 2001) and slightly higher than the Spanish Purebred horse (155-158 cm, Molina et al 1999, Gómez et al 2009) and Friesian horses (158.8; Pretorius et al 2004), but very similar to Czech cold-blooded horses (159.88; Vostrý et al 2011). Moreover, the body length of the Spanish Purebred was 159 cm (Gómez et al 2009) and for the Lipizzan horses it was 160.5 cm (Zechner et al 2001), which are both very similar to the PRMe (159 cm, Table 2).…”
Section: Resultsmentioning
confidence: 95%